"There's More to It Than Just a Box Check": Measuring Prison Climate in Three Correctional Facilities - Williams, L. Susan (International journal of offender therapy and comparative criminology, 2019)
The imperative to heed social environment and power of the situation, particularly as applied to prison settings, dates to the 1971 Stanford Prison Experiment; the widely cited study concluded that situational factors, not personality, created the damaging conditions observed. Despite critical need for research on prison climate, measurement has met stiff challenges, and little research on prison culture exists in the United States. This study applies a 17-item scale, primarily based on Essen Climate Evaluation Schema (EssenCES), an instrument validated in Australia, Germany, and the United Kingdom. It was administered to inmates and staff in three correctional facilities in the U.S. Midwest, one medium security and two maximum security. Survey results demonstrate higher levels of cohesion at the medium-security facility, but multivariate analysis suggests a much more complex relationship between facility and environment, varying particularly in response to perceived inmate threat. Qualitative data suggest that understanding these associations is vital to building socially adaptive conditions and prosocial change.